The Application of the Old Writings’ Morphology Database to Semantics Research: Verb Semantics - Jakulytė, Dalia; Pakalniškienė, Dalia (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English]The Old Writings’ Morphology Database, created by Dalia Jakulytė, is adopted for semantics research by adding a semantics module. This module is created as a table of semantic features of every word form (the main entity of the database). The places for such semantic features are reserved: Meaning, Meaning Explanation, Section / Class / Type / Group, Semantic Field and Semantic Group. To verify the semantics module, the semantics of the infixed and sta stem verbs from Knyga nobažnystės (1653) was analysed on a DB basis. The semantic functions of the verbs were established.